Fattening Arsi lambs on concentrate supplementation versus grazing - Kurtu, M.Y.; Ido, D. (1991)
A trial was conducted to study comparative difference in fattening performance of Arsi highland sheep with and without concentrate at 0.6 kg/day. Group I was supplemented with concentrate at 0.6 kg/day. Group II was not supplemented with concentrate. There were 40 lambs in each group, with almost equal initial weights of 15.6 kg in group I and 15.1 kg in group II. Final weight and average daily gain differed significantly (p < 0.01) between the groups: 34.1 kg and 23.4 kg for group I and 29.3 g and 13.39 g for group II. Rate of feed conversion of the supplemented group was 19.5 concentrate per kilogram liveweight gain; this was difficult to measure for the grazing group. Carcass traits showed a similar pattern. The supplemented group gave a heavier carcass than the unsupplemented one. This trend persisted in all carcass traits like dressing percentage and degree of fatness. The carcass from the supplemented group was so fat that it was less acceptable to the consumers while the carcass from the unsupplemented group had almost no fat. The economic feasibility, however, showed little benefit from the higher level of concentrate feeding to lambs of Arsi sheep.